2022
DOI: 10.12659/ajcr.936836
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Case of Mirizzi Syndrome Presenting as Painless Jaundice

Abstract: Patient: Male, 60-year-old Final Diagnosis: Mirizzi syndrome Symptoms: Dark stools • jaundice • painless jaundice Medication: — Clinical Procedure: ERCP with stent placement • spyglass cholangioscopy Specialty: Gastroenterology and Hepatology Objective: Unusual clinical course Background: Isolated painless jaundice is an uncommon presenting sign for Mirizzi syndrome, which is typically characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…It appears in about 0.35% of surgical cholecystectomies [ 6 ]. There may be a slight tendency for females and older populations, but recent studies have shown no male or female predilection [ 3 ]. More than 25% of MS patients are at risk for gallbladder cancer [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears in about 0.35% of surgical cholecystectomies [ 6 ]. There may be a slight tendency for females and older populations, but recent studies have shown no male or female predilection [ 3 ]. More than 25% of MS patients are at risk for gallbladder cancer [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…This condition is triggered by the presence of a gallbladder neck stone or a cystic duct stone, which, with or without a cholecystocholedochal fistula, exerts pressure on the common hepatic duct [ 2 ]. In the United States, approximately 20 million people are afflicted by cholelithiasis, and MS is an infrequent complication, affecting approximately 0.1% of these individuals [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…SpyGlass requires only one surgeon to operate and directly visualize all bile ducts, which enables one surgeon to perform definitive diagnosis and treatment in a single surgery. The SpyGlass surgery has been validated to be clinically feasible, which not only can be used for clinical diagnosis but also provides sufficient samples for histological analysis and successfully guides electrohydraulic and laser lithotripsy[ 10 - 14 ]. Electrohydraulic lithotripsy relies on high-pressure shock waves between working electrodes but is not operated under direct vision, thus causing the risk of bile duct injury.…”
Section: Discussionmentioning
confidence: 99%